Avaliação da estabilidade oxidativa do óleo de chia microencapsulado - Inácio, Alexandre Guimarães (2017)
Chia oil has been widely studied because of its benefits to human health, being source of important fatty acids like omega-3 and omega-6, in addition to several antioxidant compounds. However, like other oils rich in unsaturated fatty acids, it has low oxidative stability. The encapsulation of chia oil is an alternative to protect it from light and oxygen, factors that determine the beginning of degradation reactions. The impact of encapsulation on oil protection should be measured and in the study of oils and fats the techniques of thermal analysis have been gaining prominence in recent years due to the speed, precision and ease of operation. In this work, the oil of chia seeds was microencapsulated in carnauba wax and its thermal stability was evaluated. Firstly, the microparticles were characterized by Medium Infrared Spectroscopy, X-Ray Diffraction, Gas Chromatography and Scanning Electron Microscopy. A high encapsulation efficiency index (97%) was verified, presenting micrometric sizes, spherical shape without cracks. Differential Scanning Calorimetry (DSC) was used in isothermal and non-isothermal modes in order to determine the Arrhenius parameters of the natural and microencapsulated oil. It was possible to verify the effective protection of the chia oil conferred by the microparticles of carnauba wax, and an increase in the oxidative induction temperature of up to 26º C was detected in non-isothermal tests. The microparticles containing the oil were also subjected to the schaal oven test and the spectra obtained through Uv-vis were evaluated by chemometrics and determination of the extinction coefficients at 232 and 270 nm, corroborating the increase in the oxidative stability observed in the calorimetric assays.